Hubungan Perilaku 3M Plus dengan Kejadian Demam Berdarah Dengue (DBD) - Supriyadi Periatama; Rizki Muji Lestari; Dita Wasthu Prasida (Jurnal Surya Medika (JSM), 2022)
Dengue Hemorrhagic Fever (DHF) has a fast course and is often fatal because there are still many patients who die due to late treatment. The phenomenon of cases of Dengue Hemorrhagic Fever (DHF) in Central Kalimantan Province was reported to have 1,786 cases, more when compared to the number of cases of Dengue Hemorrhagic Fever (DHF) in 2018 as many as 2,222 cases, with the number of deaths in 2019 as many as 44 people, lower if compared to the number of deaths in 2018 as many as 22 people. The purpose of this study was to determine the "Relationship of 3M Plus Behavior with the Incidence of Dengue Hemorrhagic Fever (DHF)". This research method uses a literature study or method literature review. The technique of this research is that there are 6 journals that have been screened with criteria inclusion ranging from a sample of 40-138 respondents, with 2 study designs namely Cross-Sectional and Case-Control, the journal published in 2017-2021 and using the Indonesian language. Based on the results of research using Literature Review of 6 journals in behavioral analysis reveals the dominant category of respondents Plus 3M good and Genesis Dengue Hemorrhagic Fever (DHF) respondents dominant category is high and the results of the journal Statistics p = value 0.05no relationship with the behavior of the 3M Plus The incidence of Dengue Hemorrhagic Fever (DHF). The results of the analysis from 6 research journals Literature Review that the higher the behavior of 3M Plus in the incidence of Dengue Hemorrhagic Fever (DHF) and shows that there is a very significant relationship between the behavior of 3M Plus and the incidence of Dengue Hemorrhagic Fever (DHF).